All-optical Gain-clamped Erbium-doped Fiber Amplifier with Narrowband Amplified Spontaneous Emission Feedback Technique - Haoken, Huoermaiti; Harun, Sulaiman Wadi; Poopalan, Prabakaran; Ahmad, Harith (De Gruyter, 2008)
All-optical gain clamping of an erbium-doped fiber amplifier (EDFA) based on an unique narrowband amplified spontaneous emission (ASE) feedback technique is demonstrated by incorporating a series of fiber Bragg grating at the output end of the amplifier. The reflected ASE acts as an additional signal to limit the population inversion and clamps the amplifier's gain. The gain of the proposed amplifier is clamped at 26.5 dB with dynamic input signal power up to -14 dBm and gain variation of less than 0.1 dB. The corresponding noise figure is less than 6.9 dB. The absence of any oscillating laser in this technique is advantageous since it can avoid relaxation oscillation effect.